Scorched worth : a true story of destruction, deceit, and government corruption - Engel, Joel, 1952- (Encounter Books, 2018)
To effect just outcomes the justice system requires that law enforcement officers, prosecutors, and judges be committed-above all-to doing justice. Those whose allegiance is to winning, regardless of evidence, do the opposite of justice: they corrupt the system. This is the jaw-dropping story of one such corruption and its surprise ending. On Labor Day 2007, a forest fire broke out in California's eastern Sierra Nevada and eventually burned about 65,000 acres. Investigators from the California Department of Forestry and Fire Protection and the United States Forest Service took a mere two days to conclude that the liable party was the successful forest-products company Sierra Pacific Industries (SPI), founded as a tiny sawmill nearly sixty years earlier by Red Emmerson. The investigative report on the fire declared that SPI's independent logging contractor had started the conflagration by driving a bulldozer over a rock, creating a spark that flew into a pile of brush. No fire had ever been proven to start that way, but based on the report the U.S. Department of Justice and California's attorney general filed nearly identical suits against Emmerson's company. The amount sought was nearly a billion dollars, enough to bankrupt or severely damage it. Emmerson, of course, fought back. Week by week, month by month, year by year, his lawyers discovered that the investigators had falsified evidence, lied under oath, fabricated science, invented a narrative, and intentionally ignored a mountain of exculpatory evidence. They never pursued a known arsonist who was in the area that day, nor a young man who repeatedly volunteered alibis contradicted by facts. Though the government lawyers had not known at the start that the investigation was tainted, they nonetheless refused to drop the suits as the discovery process continued and dozens of revelations made clear that any verdict against Emmerson's company would be unjust. Scorched Worth is a riveting tale that dramatizes how fragile and arbitrary justice can be when those empowered to act in the name of the people are more loyal to the bureaucracies that employ them than to the people they're supposed to serve. It's also the story of a man who refused to let the government take from him what he'd spent a lifetime earning.